2004
DOI: 10.1128/aac.48.5.1837-1847.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model of Cervicovaginal Toxicity and Inflammation for Preclinical Evaluation of Topical Vaginal Microbicides

Abstract: Clinical trials evaluating the efficacy of nonoxynol-9 (N-9) as a topical microbicide concluded that N-9 offers no in vivo protection against human immunodeficiency virus type 1 (HIV-1) infection, despite demonstrated in vitro inactivation of HIV-1 by N-9. These trials emphasize the need for better model systems to determine candidate microbicide effectiveness and safety in a preclinical setting. To that end, time-dependent in vitro cytotoxicity, as well as in vivo toxicity and inflammation, associated with N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
107
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 23 publications
13
107
1
Order By: Relevance
“…Thus, to be accepted, they will need to not only to show efficacy but also to have outstanding safety profiles. The increased emphasis on early evaluation of microbicide safety that accompanied the nonoynol-9 findings is shown by recent reports describing a number of preclinical models for safety evaluation (5,13,15). In animals treated with zinc salts during the efficacy studies, there were no outward signs of adverse effects, such as irritation around the vaginal opening or altered behavior.…”
mentioning
confidence: 86%
“…Thus, to be accepted, they will need to not only to show efficacy but also to have outstanding safety profiles. The increased emphasis on early evaluation of microbicide safety that accompanied the nonoynol-9 findings is shown by recent reports describing a number of preclinical models for safety evaluation (5,13,15). In animals treated with zinc salts during the efficacy studies, there were no outward signs of adverse effects, such as irritation around the vaginal opening or altered behavior.…”
mentioning
confidence: 86%
“…Despite its in vitro antiviral activity, N-9 can be damaging to tissues both in vivo and in vitro. A recent paper by Catalone et al using a mouse model of cervicovaginal toxicity and inflammation showed that 1% N-9 intravaginal inoculation of Swiss Webster mice resulted in acute disruption of cervical epithelial cells (3). Another study utilizing an in vitro model demonstrated that a KY-N-9 formulation was 20 to 50 times more toxic than other candidate microbicides, including PRO 2000 and cellulose acetate phthalate (CAP) (6).…”
mentioning
confidence: 99%
“…Microbicides can be applied locally to the vaginal or rectal mucosa prior to or just following a high-risk sexual encounter. The term microbicide implies that the compound kills microorganisms; this is somewhat misleading, because microbicides may work in a variety of ways, including disrupting the pathogen's membrane or envelope, blocking receptor interactions essential for infection, inhibiting intra-or extracellular pathogen replication, or enhancing local, mucosal immune responses, thereby reducing susceptibility (10,22,26,30). A recent experimental microbicide strategy used CpG-containing oligonucleotides (CpG-ODN) delivered topically to the vaginal mucosa to induce a local immune response that protected against HSV-2 infection (21).…”
mentioning
confidence: 99%